Factors Associated With Adults’ Physical Activity In Bo-jongsoang District Bandung Regency - Marfian, Kenvin; Ayubi, Dian; Hadi, Ella Nurlaella (Jurnal EduHealth, 2024)
Noncommunicable diseases (NCDs) have caused high burden of mortality in Indonesia. One of the main risk factors of NCDs is physical inactivity, which has become a problem in Bandung Regency. Biological, psychological, sociodemographic, sociocultural, and built environment (BE) factors affect physical activity (PA) levels. This study seeks to understand the factors that are associated with adults’ PA in Bojongsoang District. This quantitative, observational, analytical study uses a cross-sectional design. The study population are adults aged 18-59 years old which are domiciled in Bojongsoang District, while the study sample is determined to be 250 people based on calculation of two proportion differences. Data is collected through questionnaire-based guided interview. Univariate analysis shows that the number of respondents that engage in PA at least 150 minutes/week is 69,2%. Multiple logistic regression results show that work (OR 0,555; CI 95% 0,313-0,983), private vehicle ownership (OR 4,351; CI 95% 1,188-15,940), and social support (OR 3,160; CI 95% 1,776-5,621) are associated with PA after controlling for other independent variables. Private vehicle ownership is the most dominant variable associated with adults’ PA in Bojongsoang District. Community-oriented interventions to improve PA in Bojongsoang District needs to target the workers and those who use private vehicles.